PENGEMBANGAN PENDIDIKAN KARAKTER BERWAWASAN KONSERVASI NILAI-NILAI SOSIAL - Rachman, Maman (Faculty of Social Science, Universitas Negeri Semarang, 2013)
Nation-building and character development has been became the commitment of the founding fathers of Indonesia since homeland standing. Given the Pancasila philosophy is basic and the nation, the Pancasila is the basic reference for building a nation of character. In this journey, the effort going tides. Therefore, the educational character of the conservation- minded social values are very important. Character is formed due to the repetitive actions that it becomes a habit that internalization in man’s life. Conservation has meaning preservation, restoration, reconstruction, adaptation and rehabilitation of not only physical but also social values. Conservation social values is an effort to preserve, conserve, and refused to accept a set of values embraced the community of what constitutes good and bad. Social value can be identified by observing and social values based on characteristics such as social interaction, transformation, the process of learning, fulfillment, diversity, acceptance, influencet and assumptions. Studying social values would be very beneficial if the value is applied in everyday life.